2021
DOI: 10.1172/jci.insight.146416
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte released HERV-K dUTPase engages TLR4 and MCAM causing endothelial mesenchymal transition

Abstract: Previously we reported heightened expression of human endogenous retroviral protein HERV-K deoxyuridine triphosphate nucleotidohydrolase (dUTPase) in circulating monocytes and pulmonary arterial (PA) adventitial macrophages of PA hypertension (PAH) patients. Furthermore, recombinant HERV-K dUTPase increased IL6 in PA endothelial cells (PAECs) and caused pulmonary hypertension in rats. Here we show that monocytes overexpressing HERV-K dUTPase as opposed to GFP, can release HERV-K dUTPase in extracellular vesicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…HERV-K dUTPase did not induce an elevation in PKR or RIG-1 mRNA or in NE protein (Figure E5C and E5D in the Online Data Supplement). The dose of dUTPase chosen was based upon previous studies by our group showing the impact of dUTPase on cytokine release (37) and EndMT (38). We then determined whether the increase in vinculin could explain the increase in adhesion and the reduction in migration.…”
Section: Transcriptomic Analysis Reveals An Antiviral Signature In Pa...mentioning
confidence: 99%
“…HERV-K dUTPase did not induce an elevation in PKR or RIG-1 mRNA or in NE protein (Figure E5C and E5D in the Online Data Supplement). The dose of dUTPase chosen was based upon previous studies by our group showing the impact of dUTPase on cytokine release (37) and EndMT (38). We then determined whether the increase in vinculin could explain the increase in adhesion and the reduction in migration.…”
Section: Transcriptomic Analysis Reveals An Antiviral Signature In Pa...mentioning
confidence: 99%
“…In advanced PAH, NF-κB is active in PAEC, PASMC and perivascular macrophages and lymphocytes of large and small pre-capillary vessels and is correlated with expression of pro-inflammatory cytokines (131). In PAEC, NF-κB contributes to leucocyte adhesion and inflammation facilitating EndMT (132). In contrast, genetic and pharmacological inhibition of NF-κB reversed and prevented experimental PAH in rodent models, respectively (133,134).…”
Section: Nf-kbmentioning
confidence: 99%
“…This results in a proliferative, hypermigratory phenotype (138). Also Otsuki et al showed, that PAECs stimulated with human endogenous retrovirus K (HERV-K) dUTPase have a TLR4-STAT1-dependent inflammatory response (132).…”
Section: Stat1mentioning
confidence: 99%
“…HERV deoxyuridine triphosphate nucleotidohydrolase (dUTPase) can trigger innate and adaptive immune responses [ 139 ]. In pulmonary arterial hypertension (PAH), the HERV-K dUTPase activates B cells, elevates cytokines in monocytes and pulmonary arterial endothelial cells, and increases pulmonary artery vulnerability to apoptosis, contributing to sustained inflammation and immune dysregulation [ 140 ].…”
Section: Transcriptional Dysregulation Of Ervs In Human Diseasesmentioning
confidence: 99%